Soft robot for impulsive hopping drive - Khoo, Kar Keng (2018)
Arch flexure dielectric elastomer finger (DEMES) provides fast-response and high- strength. It is based on DEAs segmented by polyimide frame, bonded to a passive PVC frame at width mismatch. Bending moment from active layer is balanced by reactive moment by passive layer, forming a longitudinally curled finger. Voltage application releases active layer’s tension, uncurling the finger. This project reports the locomotion analysis of impulsive hopping drive soft robot with inch-worm-like locomotion. DEMES-roller and 2-DEMES configurations were studied with the former having higher speed. For DEMES-roller configuration, the frequency of 15Hz provided fastest locomotion speed at 0.42BL/s. DEMES model was also presented to predict experimental results with good conformation. Better DEMES design with cleaner fabrication, less motion-constraint, less-distortion and longer lifetime (3-week) was reported. The performance improvement DEMES such as consistency, full-uncurling ability at static actuation and better dynamic response was documented. In static test, 68.27° mean tip angle change was recorded, comparable to previous design with similar configurations. In dynamic test, 3Hz and 9Hz of resonant frequencies were recorded with 127.13° maximum tip angle change at 9Hz. Dynamically, the curling and uncurling rise times were improved to 38ms and 42ms respectively.